Port site intramuscular abscess from retained gallstone post laparoscopic cholecystectomy – an unusual complication. Issue 1 (4th January 2023) - Syed, Faisal; Quah, Gaik Si; Di Re, Angelina
Abstract: Perforation of the gallbladder and the spillage of gallstones can be a cause of ongoing morbidity and mortality in patients post cholecystectomy. We report on an unusual case of a 58-year-old male who developed a right upper quadrant lump 8 years after laparoscopic cholecystectomy which was eventually determined to be an abscess from a retained gallstone that had become embedded in the musculature of his abdominal wall. We have also discussed some of the considerations taken in the surgical management of this case.